IMPLEMENTASI PROGRAM KULIAH KERJA NYATA UNIVERSITAS PANCA BHAKTI DI DESA LIMBUNG, KECAMATAN SUNGAI RAYA - Anggraini, Ika Muthya (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
Abstract Community Service Program (KKN) is a form of implementation of the Tri Dharma of Higher Education in the aspect of community service. The Panca Bhakti University (UPB) Community Service Program Group 8 was conducted in Limbung Village, Sungai Raya District, Kubu Raya Regency for 30 days, involving 18 students. The program was designed based on field observations that identified several problems, such as low awareness, cleanliness, unorganized regional administration, adolescents' limited understanding of the dangers of bullying, and the need for support for MSMEs and sports facilities. Various programs implemented included environmental cleanups, outreach on stopping bullying and juvenile delinquency, the creation of alley and house number signs, tree planting, volleyball court repairs, and the creation of MSME banners. The results demonstrated increased community awareness, strengthened community togetherness, increased youth understanding, and tangible support for the local economy. Overall, this Community Service Program had a positive physical and social impact and encouraged sustainable change in Limbung Village. Keywords: Community Service Program, community service, Limbung Village, Kubu Raya Regency, empowerment, participatory.